2024
DOI: 10.1371/journal.pone.0297179
|View full text |Cite
|
Sign up to set email alerts
|

Does increasing biodiversity in an urban woodland setting promote positive emotional responses in humans? A stress recovery experiment using 360-degree videos of an urban woodland

Simone Farris,
Nicola Dempsey,
Kirsten McEwan
et al.

Abstract: Green spaces can support human stress reduction and foster positive emotional well-being. Previous research has suggested that biodiversity (i.e. the variety of species of plants and animals in a given location) can enhance recovery from stress even further. However, there is limited experimental evidence testing this hypothesis and results, to date, have been mixed. This study aimed to provide further understanding of the role of biodiversity (actual or perceived) on human well-being by experimentally manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Studies have also juxtaposed the associations of measured and perceived biodiversity with mental well-being. In these cases, perceived biodiversity was found to have a stronger effect on mental well-being than measured biodiversity (Cameron et al, 2020; Dallimer et al, 2012; Farris et al, 2024; Rozario et al, 2024; Schebella et al, 2019; Zumhof, 2019). Indeed, Rozario et al (2024), Farris et al (2024) and Zumhof (2019) only found significant mental well-being effects for perceived biodiversity.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies have also juxtaposed the associations of measured and perceived biodiversity with mental well-being. In these cases, perceived biodiversity was found to have a stronger effect on mental well-being than measured biodiversity (Cameron et al, 2020; Dallimer et al, 2012; Farris et al, 2024; Rozario et al, 2024; Schebella et al, 2019; Zumhof, 2019). Indeed, Rozario et al (2024), Farris et al (2024) and Zumhof (2019) only found significant mental well-being effects for perceived biodiversity.…”
Section: Introductionmentioning
confidence: 87%
“…In these cases, perceived biodiversity was found to have a stronger effect on mental well-being than measured biodiversity (Cameron et al, 2020; Dallimer et al, 2012; Farris et al, 2024; Rozario et al, 2024; Schebella et al, 2019; Zumhof, 2019). Indeed, Rozario et al (2024), Farris et al (2024) and Zumhof (2019) only found significant mental well-being effects for perceived biodiversity. A more nuanced differentiation between measured and perceived biodiversity is hence needed to understand their respective effects on mental well-being.…”
Section: Introductionmentioning
confidence: 87%